Quantifying and mapping species threat abatement opportunities to support national target setting. Issue 1 (13th December 2022) - Mair, Louise; Amorim, Eduardo; Bicalho, Monira; Brooks, Thomas M.; Calfo, Vincente; de T. Capellão, Renata; Clubbe, Colin; Evju, Marianne; Fernandez, Eduardo P.; Ferreira, Gláucia C.; Hawkins, Frank; Jiménez, Randall R.; et al.
Abstract: The successful implementation of the Convention on Biological Diversity's post‐2020 Global Biodiversity Framework will rely on effective translation of targets from global to national level and increased engagement across diverse sectors of society. Species conservation targets require policy support measures that can be applied to a diversity of taxonomic groups, that link action targets to outcome goals, and that can be applied to both global and national data sets to account for national context, which the species threat abatement and restoration (STAR) metric does. To test the flexibility of STAR, we applied the metric to vascular plants listed on national red lists of Brazil, Norway, and South Africa. The STAR metric uses data on species' extinction risk, distributions, and threats, which we obtained from national red lists to quantify the contribution that threat abatement and habitat restoration activities could make to reducing species' extinction risk. Across all 3 countries, the greatest opportunity for reducing plant species' extinction risk was from abating threats from agricultural activities, which could reduce species' extinction risk by 54% in Norway, 36% in South Africa, and 29% in Brazil. Species extinction risk could be reduced by a further 21% in South Africa by abating threats from invasive species and by 21% in Brazil by abating threats from urban expansion. Even with different approaches to red‐listing among countries, the STAR metric yielded informative results that identified where the greatest conservation gains could be made for species through threat‐abatement and restoration activities. Quantifiably linking local taxonomic coverage and data collection to global processes with STAR would allow national target setting to align with global targets and enable state and nonstate actors to measure and report on their potential contributions to species conservation.